Towards a unifying mechanism for ClpB/Hsp104-mediated protein disaggregation and prion propagation - Haslberger, Tobias; Bukau, Bernd; Mogk, Axel (Biochemistry and cell biology, 2010)
The oligomeric AAA+ chaperones ClpB/Hsp104 mediate the reactivation of aggregated proteins, an activity that is crucial for the survival of cells during severe stress. Hsp104 is also essential for the propagation of yeast prions by severing prion fibres. Protein disaggregation depends on the cooperation of ClpB/Hsp104 with a cognate Hsp70 chaperone system. While Hsp70 chaperones are also involved in prion propagation, their precise role is much less well defined compared with its function in aggregate solubilization. Therefore, it remained unclear whether both ClpB/Hsp104 activities are based on common or different mechanisms. Novel data show that ClpB/Hsp104 uses a motor threading activity to remodel both protein aggregates and prion fibrils. Moreover, transfer of both types of substrates to the ClpB/Hsp104 processing pore site requires initial substrate interaction of Hsp70. Together these data emphasize the similarity of thermotolerance and prion propagation pathways and point to a shared mechanistic principle of Hsp70-ClpB/Hsp104-mediated solubilization of amorphous and ordered aggregates.
This paper is one of a selection of papers published in this special issue entitled 8th International Conference on AAA Proteins and has undergone the Journal's usual peer review process
Gesehen am 27.03.2023